VARIABILITY OF MORPHOLOGICAL AND ANATOMICAL FEATURES OF SCOTS PINE NEEDLES - Tereshchenko, L. I. (Forestry and Forest Melioration, 2018)
Introduction Many researchers have shown in their papers that the features of morphological and anatomical structure of needles are largely dependent on climate and weather, mineral, air and water nutrition, height and age of trees and other environmental factors, and at the same time, the formation of morphological and anatomical characteristics is under genetic control. The most accessible for study anatomical indicator is the number of resin canals since it is considered sufficiently stable characteristic. Up-to-date investigations of Pinus sylvestris L. assimilation system in Ukraine are few and most of them are related to the study of characteristics of stands being in contrasting growth conditions. Such works, in our opinion, do not cover the whole variety, which is observed in size, number and location of resin canals in the needles of pine trees in similar types of site conditions, but in different natural areas. The aim of this study is to explore the features of morphological and anatomical structure of needles in pine stands and to assess the level of studied characteristics variability in different soil and climatic conditions. Materials and Methods The results of research of the morphological and anatomical structure of needles in Sumy (Polissya), Kirovohrad (southern Steppe), Kharkiv (southern Steppe, Steppe) and Luhansk (Steppe) areas from 2004 to 2015 were analyzed. The total number of sites where the needles were prepared is 15. The branches with needles were taken from 17-30 trees in each stand. Prior to begining the morphological and anatomical study the branches have been preserved in the freezer. For each tree the linear dimensions and anatomy of needles have been determined at least at 20 needles of one year old. On middle slice the total number of needle resin canals, their homogeneity in sizes and position were examined. The data for each quantitative characteristic was statistically processed by a computer program Microsoft Excel. Results The length of the needles of pine trees of stands aged from 13 to 137 years old of the natural and artificial origin varies from 30 to 125 mm, an average of 65.8 to 79.1 mm. In conditions of Polissya the average index is 67.6 mm, in the Forest-Steppe it is 68.8 mm and in the northern Steppe 75.6 mm. The length of 1-year old needles of pine chalk ecotype (NNP "Svyati Hory") is 47.4 mm (2 years old – 64.7 mm). Variability of parameter between trees within the stands is from 12 to 23 %; between stands it is 9.4%. The average number of resin canals in the needles within stands is ranging from 11.4 to 16.0 pieces., in average for all investigated stands it accounts for 13.9 pieces. There can be from 3 to 15 resin canals on the convex side of needles and from 1 to 10 pieces on a flat side. The smallest number of resin canals in the needles is 3 pieces, the maximum one is 24 pieces. Needles of pine of Polissya origin and young trees have less of resin canals. The coefficient of variation between the stands is 9 % and between the trees within stands it is from 12.3 to 25.0 %. In the case of gathering the needles only from female shoots the correlation “needle length - the number of resin canals” is direct and medium (r = 0,44), in other cases (vegetative and male types of shoots, significant age of stand) such a correlation is absent. It was determined that the length of the needles and the number of resin canals in it are not practically related to the growth characteristics of trees. A significant proportion of needles sample from southern steppe and from steppe zones have the parenchymal and transitional resin canals, the last also vary in size. The tendency to increase the proportion of trees in the samples of which the parenchymal and transitional type of resin canals (from 26 to 78%) are presented was noted in the direction of Polissya – Forest-Steppe – Steppe. Parenchymal channels of the third part of samples are small in size. Usually there are from 1 to 3 transient and parenchymal canals in the needle, more rarely there are 4-6 pieces. Increasing the number of transient and parenchymal resin canals in the needles in some way is related to the deteriorating growth conditions, that manifests itself in thickening of needles and its bluish color. Needles of pine trees from Polissya (120 years old) have by 2.8 pieces (28%) on average more resin canals than its seed progeny in the provenance tests of second-generation (20 years old), but the proportion of trees with the presence of transients and parenchymal types of resin canals in the needles (26,0 % in comparison with 29,4 % in the progeny) is less. The progeny is being in process of a gradual adaptation to the conditions of growth in the southern Forest- Steppe. Conclusions The average length of the needles of pine trees stands of natural and artificial origin in Polissya is 67.6 mm, in the Forest-Steppe it is 68.8 mm, in the northern Steppe 75.6 mm and of pine chalk ecotype (northern Steppe) it accounts for 47.4 mm. Variability of parameters of the needle length and resin canals number in conditions of fresh hygrotop between stands is low; at the individual level within stands, variability is medium and high. Number of pine needles resin canals in investigated stands is from 11.4 to 16.0 pieces on average, including the convex side – 8.2-10.7 pieces and flat side – 3.2- 5.3 pieces The needles of Polissya origin pine and young trees have less of resin canals. The length of the needles and the number of resin canals there are practically not correlated with growth characteristics of trees. The tendency to increase the proportion of trees in the samples of which the parenchymal and transitional type of resin canals (from 26 to 78%) are presented was noted in the direction of Polissya – Forest-Steppe – Steppe. The needles of pine trees from Polissya have more resin canals (by 28%) than its seed progeny in the provenance tests of second-generation in the Forest-Steppe conditions, but the proportion of trees with the presence of transients and parenchymal types of resin canals in the needles is less by 3.8 %.